The intentional spectrum and intersubjectivity : phenomenology and the Pittsburgh Neo-Hegelians - Barber, Michael D., 1949- (Series in Continental thought., 2011)
World-renowned analytic philosophers John McDowell and Robert Brandom, dubbed "Pittsburgh Neo-Hegelians," recently engaged in an intriguing debate about perception. In The Intentional Spectrum and Intersubjectivity Michael D. Barber is the first to bring phenomenology to bear not just on the perspectivesof McDowell or Brandom alone, but on their intersection. He argues that McDowell accounts better for the intelligibility of empirical content by defending holistically functioning, reflectively distinguishable sensory and intellectual intentionalstructures. He reconstructs dimensions implicit.